Activity of Delafloxacin and Comparator Fluoroquinolones against Multidrug-Resistant Pseudomonas aeruginosa in an In Vitro Cystic Fibrosis Sputum Model - Vaughn D. Craddock; Evan L. Steere; Hannah Harman; Nicholas S. Britt (MDPI AG, 2023)
Delafloxacin (DLX) is a recently approved fluoroquinolone with broad activity against common cystic fibrosis (CF) pathogens, including multidrug-resistant Pseudomonas aeruginosa (MDR-Psa). Delafloxacin has been previously shown to have excellent lung and biofilm penetration and enhanced activity at lower pH environments, such as those that would be observed in the CF lung. We analyzed six Psa strains isolated from CF sputum and compared DLX to ciprofloxacin (CPX) and levofloxacin (LVX). Minimum inhibitory concentrations (MICs) were determined for DLX using standard culture media (pH 7.3) and artificial sputum media (ASM), a physiologic media recapitulating the CF lung microenvironment (pH 6.9). Delafloxacin activity was further compared to CPX and LVX in an in vitro CF sputum time-kill model at physiologically relevant drug concentrations (Cmax, Cmed, Cmin). Delafloxacin exhibited 2- to 4-fold MIC reductions in ASM, which corresponded with significant improvements in bacterial killing in the CF sputum time-kill model between DLX and LVX at Cmed (p = 0.033) and Cmin (p = 0.004). Compared to CPX, DLX demonstrated significantly greater killing at Cmin (p = 0.024). Overall, DLX demonstrated favorable in vitro activity compared to alternative fluoroquinolones against MDR-Psa. Delafloxacin may be considered as an option against MDR-Psa pulmonary infections in CF.